2018
DOI: 10.14710/geoplanning.5.1.17-34
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Predicting Land Use-Land Cover (Lulc) Changes Within and Around Krau Wildlife Reserve (Kwr) Protected Area in Malaysia Using Multi-Temporal Landsat Data

Abstract: Natural and anthropogenic activities surrounding a Protected Area (PA) may cause its natural area to change in terms of Land Use-Land Cover (LULC). Thus, there is need of environmental change monitoring within and around PA because of its significant values to ecosystem at conservation scales. Effects and influences of local community within and around PA turn into the major problems for natural resource and conservations management as well as environmental impact assessment. Ascertaining the complex interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The KWR aims to conserve the wildlife, particularly Gaur, which may be found in huge populations in places previously inhabited by aborigenes. An Institute of Biodiversity and the National Elephant Conservation Centre are located in the southern half of the reserve, accessible through Lanchang [11].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The KWR aims to conserve the wildlife, particularly Gaur, which may be found in huge populations in places previously inhabited by aborigenes. An Institute of Biodiversity and the National Elephant Conservation Centre are located in the southern half of the reserve, accessible through Lanchang [11].…”
Section: Study Areamentioning
confidence: 99%
“…Maintaining the wildlife and its habitat through PAs will contribute to the SDGs, especially the 13th and 15th goals that focus on climate change and life on land [9]. Many studies using remote sensing and Geographical Information Systems (GIS) have shown the threats of endangered species and encroachment of PAs [10,11]. A study has been conducted by [12] utilizing Landsat data and machine learning algorithms to perform KWR mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Ground information can be acquired from a wide area in a short time via remote sensing. It collects spatial data without any direct contact and has been put to use in fields such as activities as biomass estimation, oil palm disease detection, urban areas, agricultural land, object detection, hazard prediction, and biodiversity monitoring [218]. Numerous studies on oil palm plantation mapping have been carried out in response to the increased demand for oil palm products using remote sensing [136] .…”
Section: ) Effect Of Climate Change In Oil Palm Cultivationmentioning
confidence: 99%
“…Remote Sensing (RS) and Geographic Information System (GIS) are effective techniques for estimating forest cover change. RS and GIS techniques are used extensively for generating valuable information on forest cover in the tropical areas, land use changes over large areas 14,15,16,17,18,19 and protected areas 12,20,21,22,23 . So far, habitat loss in Kameng and Sonitpur Elephant Reserves 24 , large-scale deforestation in Sonitpur district 15 , and land use/land cover change and fragmentation in Nameri Tiger Reserve 12 are available.…”
Section: Introductionmentioning
confidence: 99%